Antiferromagnetic Piezospintronics. (4th April 2019) - Liu, Zhiqi; Feng, Zexin; Yan, Han; Wang, Xiaoning; Zhou, Xiaorong; Qin, Peixin; Guo, Huixin; Yu, Ronghai; Jiang, Chengbao
Abstract: Antiferromagnets naturally exhibit three obvious advantages over ferromagnets for memory device applications: insensitivity to external magnetic fields, much faster spin dynamics (≈THz), and higher packing density due to the absence of any stray field. Recently, antiferromagnetic spintronics has emerged as a cutting‐edge field in the magnetism community. The key mission of this rapidly rising field is to steer the spins or spin axes of antiferromagnets via external stimuli and then realize advanced devices based on their physical property changes. Herein, the state‐of‐the‐art of antiferromagnetic spintronics is presented. Subsequently, the history of ferromagnetic/ferroelectric multiferroic composites is briefly revisited. Finally, an ultralow‐power, long‐range, and magnetic‐field‐insensitive approach for harnessing antiferromagnetic spins based on recent experimental progress, i.e., piezoelectric strain control, is introduced. Relevant theoretical and experimental studies have formed an attractive new branch in antiferromagnetic spintronics, which is dubbed "antiferromagnetic piezospintronics." Abstract : A new concept—antiferromagnetic piezospintronics —is proposed based on recent experimental and theoretical progress on the piezoelectric strain control of antiferromagnetic spins, which are rather difficult to manipulate with magnetic fields. This concept emphasizes a highly efficient, super‐low‐power, long‐range, and magnetic‐field‐insensitive approach for harnessing spins in antiferromagnets and represents a new branch in emerging antiferromagnetic spintronics.